Compiling a Model of Managers' Professional Meritocracy Based on Islamic and Iranian Teachings - Taghipour, Azar (2020)
The purpose of this study is to develop a model of professional meritocracy of managers based on Iranian and Islamic teachings. The research method is mixed (qualitatively quantitative) of the type of successive exploratory designs. In the qualitative section, using the library method and mining texts, the concepts related to the indicators of professional competence of organizational managers were examined. The statistical population in this section was 47 educational management experts who were selected by purposive sampling method and using the analysis of semi-open interview results and content analysis method, concepts were drawn in the form of a network of themes. The tools for collecting research information in the qualitative section were sources, interviews and documents (research reports, etc.) that the participatory feedback method was used to validate the validity and reliability analysis. In order to analyze the qualitative data, inductive content analysis based on open coding was used. In the quantitative part, data collection was based on a researcher-made questionnaire. In this part, a one-sample t-test was used and the statistical population of this section was 213 And were bred in Bushehr province that multi-stage cluster sampling method was used to select quantitative statistical samples. To validate the reliability of the questionnaire in this section, Cronbach's alpha coefficient was used, the reliability of which was 0.78, and its face and content validity was confirmed by experts. Data analysis in the qualitative domain was based on content analysis and in the quantitative domain was done using statistical software and factor analysis method. The results showed that the development of human resource management model with qualification criteria in accordance with Islamic and Iranian teachings, organizational planning based on "competence", matching capabilities and competencies with jobs and managements should be done carefully and only under legal and ethical criteria.